Materials’ characterization and properties of multiwalled carbon nanotubes from industrial waste as electromagnetic wave absorber - Fadzidah, Mohd Idris; Khamirul Amin, Matori; Ismayadi, Ismail; Idza Riati, Ibrahim; Rodziah, Nazlan; Farah Nabilah, Shafiee; Mohd Shamsul Ezzad, Shafie (Springer Nature Switzerland, 2022)
The development of high-frequency devices has attracted more research interest in electromagnetic wave–absorbing materials having lightweight, low fller content, thin thickness, minimum refection loss and broad absorption bandwidth. Nevertheless, none of the materials uses steel waste (mill scale) as a potential lowcost catalyst to synthesize carbon nanotubes (CNT) as an electromagnetic (EM) wave absorber. Hence, multiwalled carbon nanotubes loaded in epoxy resin with an increasing polymer composite thickness of 1 mm, 2 mm, and 3 mm were introduced in this study.